THE MEDIATING ROLE OF ATTITUDE IN IMPULSE BUYING - Purwianti, Lily; Yulianto, Edy; Lie, Deviana (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
This research aims to investigate the impact of influencer credibility on consumer behavior, particularly in the context of the urge to make impulsive purchases. The subjects of this study are individuals who have made unplanned purchases through online shops. The outer model measurement and hypothesis testing (direct and indirect) were conducted on a data sample of individuals who made unplanned online purchases, using the statistical tool SEM-PLS. Data were collected through a questionnaire distributed online via Google Forms, utilizing non-probability sampling techniques and the purposive sampling method, with a total sample size of 310 respondents. The study found several hypotheses indicating negative and insignificant effects, including the hypothesis of influencer credibility on attitude, the hypothesis of perceived usefulness on attitude, the hypothesis of influencer credibility on the urge to buy impulsively mediated by attitude, and the hypothesis of perceived usefulness on the urge to buy impulsively mediated by attitude. However, other hypothesis tests showed significant results. This research provides deep insights into how these variables can be used in marketing strategies to drive impulsive purchases and highlights the importance of understanding the psychological dynamics behind consumer behavior in the context of social media.